On Some Examples of Trajectories in <semantics>R</semantics>7 - Ana Irina Nistor (Mathematics, 2022)
In this paper we study the magnetic trajectories as the solutions of the Lorentz equation defined by the cross product corresponding to the 7-dimensional Euclidean space. We find several examples of such trajectories and moreover, we strongly motivate our results making a comparison with the 3-dimensional Euclidean case, ambient space which was among the first ones approached in the study of magnetic trajectories.